Field Theoretic Method in Phase Transformations - Umantsev, Alexander; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The continuum, field theoretic method of study of phase transformations in material systems, also known as "phase field", allows one to analyze different stages of transformations on the unified platform. It has received significant attention in the materials science community recently due to many successes in solving or illuminating important problems. This book will address fundamentals of the method starting from the classical theories of phase transitions, the most important theoretical and computational results, and some of the most advanced recent applications. Field Theoretic Method in Phase Transformations can be used as an introduction for those new to the field or as a guide for a seasoned researcher. It is also of interest to researchers interested in the history of physics.
Landau Theory of Phase Transitions -- Heterogeneous Equilibrium Systems -- Dynamics of Homogeneous Systems -- Evolution of Heterogeneous Systems -- Thermo-Mechanical Analogy -- Thermodynamic Fluctuations -- More Complicated Systems -- Thermal Effects: Coupling to (3z(BHydrodynamic(3y (BVariables -- Transformations in Real Materials -- Extensions of the Method.s
Keywords: Physics; Materials; Physics; Condensed Matter Physics; Theoretical, Mathematical and Computational Physics; Materials Science, general